A Case of Deficiency of Adenosine Deaminase 2: 28 years of Diagnostic Challenges - Clara Pardinhas (Karger Publishers, 2021)
Deficiency of adenosine deaminase 2 (DADA2) is a unique monogenic autoinflammatory disease caused by autosomal recessive loss-of-function mutations in the CECR1 gene which presents as childhood-onset small- and medium-vessel vasculitis. Previously, many of these patients were misdiagnosed and thought to have clinical features of systemic polyarteritis nodosum, which negatively influenced its outcome, since TNF inhibitors seem to have efficacy on the vasculitic phenotype of DADA2. We present a case of a 28-year-old woman with a lifelong unknown syndrome and unique clinical manifestations recently recognized as DADA2. The first manifestation, at 3 months of age, was an episode of facial paralysis during which renovascular hypertension was diagnosed. Later, she developed episodes of prolonged fever, polyarthritis, Raynaud’s phenomenon, gastrointestinal bleeding, and intracerebral hemorrhage. This inflammatory state ultimately led to the development of amyloid A amyloidosis and renal insufficiency.